Essays on product quality in commercial aviation - Yimga, Jules O. (Kansas State University, 2016)
This dissertation consists of three essays on product quality in commercial aviation. Since the mid-1990s, major airlines that serve the U.S. domestic market have increasingly found it appealing to form alliances. Amidst the recent emergence of airline alliance formation, this dissertation has sought to answer questions on the product quality implications of policies regarding cooperation among airlines in the U.S. domestic air travel industry. A challenge that empirical work faces in studying the relationship between airline alliances and product quality is to find reasonable measure(s) of product quality. The first essay sheds light on whether the route network integration that comes with an airline alliance provides sufficient extra incentive to partner carriers to improve their flight routing quality. Evidence suggests that routing quality for Delta/Continental/Northwest's--our alliance of interest--products decreases in markets where pre-alliance competition among alliance partners exists, resulting in substantial negative welfare effects for passengers. In fact, routing quality for Delta/Continental/Northwest products decreased by 0.256% below the mean routing quality of the entire sample's products. More interestingly, the codeshare effects in specific markets where the alliance firms competed prior to the alliance, are also negatively associated with routing quality of the alliance firms' products, resulting in a fall in consumer utility of $0.5 per consumer. The second essay explores the potential relationship between on-time performance and airline code-sharing. Although flight delay has always received much attention, we are unaware of any empirical research that measures the on-time performance effects of airline alliances. We empirically investigate the on-time performance effects of the largest U.S. domestic alliance that began in June 2003--an alliance between Delta Air Lines, Northwest Airlines and Continental Airlines. We find evidence that code-sharing improves alliance partners' on-time performance and that the size of the alliance effect on on-time performance depends on pre-alliance competition in a market, with the effect being larger in markets where the partners competed in prior to the alliance. Using a structural econometric model, the third essay attempts to provide an alternative explanation to a long-standing question: why are airlines late? Airlines usually claim that air travel delays are out of their control, placing the blame on adverse weather or air traffic control as the most common reasons. Despite these claims, data on causes of flight delay reveal that the share of delay caused by weather and air traffic control has been on the decline while the share of delay caused by airlines has been on the rise. This suggests that on-time performance improvement is well within the reach of carriers. We investigate why airlines have little or no incentive to improve on-time performance. We also measure the cost of delay borne by consumers in terms of how much monetary value they are willing to pay to avoid delay. We find that consumers are willing to pay $0.78 for every minute of arrival delay which after extrapolation, amounts to consumer welfare effects of $1.76 billion. Our findings suggest that airlines have little to no incentive because their markups do not increase when they improve on-time performance. In fact, the marginal increase in price resulting from on-time performance improvement is offset by an increase in marginal cost causing a zero net effect on markup.
Keywords: Airline Routing Quality; Airline Code-sharing; Airline On-Time Performance; Airline Product Quality; Airline Competition